2021
DOI: 10.20473/amnt.v5i1.2021.31-40
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Obesitas pada Guru Sekolah Perempuan serta Relevansi dengan PTM Selama Pandemi Covid-19

Abstract: Background: The prevalence of obesity in the world is getting higher, so it becomes a severe health problem. Some factors that contribute to the problem of obesity are increased calorie intake, including the consumption of junk food and sedentary, and low physical activity. School teachers are one of the most crucial labor elements in improving the human development indeks.Objectives: The study aims to determine the risk factors for obesity in female teachers as well as some non-communicable health problems du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…Pandemi Covid-19 telah membuat perubahan pola kehidupan pada berbagai sektor termasuk aktivitas serta pola konsumsi yang tidak terkontrol, seperti sedentary dan makan makanan cepat saji 7 . Faktor-faktor tersebut bila berlangsung secara berkesinambungan, maka hal tersebut memungkinkan terjadinya risiko obesitas 8 . Kelebihan berat badan (IMT 25 -26,9 Kg/m 2 ) atau obesitas (IMT ≥ 27 Kg/m 2 ) telah dianggap menjadi faktor risiko utama terhadap beberapa penyakit kronis termasuk penyakit jantung koroner, hipertensi, kolesterol, dan diabetes pada masa pandemi Covid-19 9 .…”
Section: Pendahuluanunclassified
“…Pandemi Covid-19 telah membuat perubahan pola kehidupan pada berbagai sektor termasuk aktivitas serta pola konsumsi yang tidak terkontrol, seperti sedentary dan makan makanan cepat saji 7 . Faktor-faktor tersebut bila berlangsung secara berkesinambungan, maka hal tersebut memungkinkan terjadinya risiko obesitas 8 . Kelebihan berat badan (IMT 25 -26,9 Kg/m 2 ) atau obesitas (IMT ≥ 27 Kg/m 2 ) telah dianggap menjadi faktor risiko utama terhadap beberapa penyakit kronis termasuk penyakit jantung koroner, hipertensi, kolesterol, dan diabetes pada masa pandemi Covid-19 9 .…”
Section: Pendahuluanunclassified
“…Berdasarkan hasil Riskesdas 2018 kejadian stunting di Indonesia masih tinggi meski sudah terjadi penurunan dari 37,2% menjadi 30,8% 3 . Stunting menjadi masalah global karena selain berdampak terhadap kesehatan jangka pendek juga berdampak jangka panjang seperti perkembangan kognitif yang terganggu 4 dan performa pendidikan 5 , potensi sumber daya manusia dewasa yang lebih rendah 6 , efek morbiditas dengan peningkatan resiko penyakit tidak menular dan obesitas 7,8 .…”
Section: Pendahuluanunclassified
“…Sedentary behaviors need to be limited because several studies have shown that this behavior is a factor in obesity, which increases the risk of various health issues. 33,5% of the population has physical activity, which is included in the lower category (Kemenkes RI, 2018;Rahmad, 2021). Pregnant women may engage in sedentary or low physical activity.…”
Section: Introductionmentioning
confidence: 99%